Implementasi Pembelajaran Berdiferensiasi Dalam Kurikulum Merdeka Pada Mata Pelajaran Sejarah Di SMA Negeri 22 Surabaya - Sindy Dwi Jayanti; Agus Suprijono; M. Jacky (LP. Ma'arif Janggan Magetan, 2023)
Merdeka Curriculum provides flexibility in the implementation of education. Differentiate learning is one example of teacher flexibility to design learning activities that are matched to the learning needs of students. The purpose of this research is to find out the implementation of differentiated learning in the Merdeka Curriculum in history subjects at SMA Negeri 22 Surabaya. This research uses case study and interview methods as data collection techniques. The results of the study show three major points, 1) diagnostic assessments are carried out without fixed standards, 2) differentiation of content, processes and products is implemented that focuses on student’s profiles or learning styles, 3) evaluation and follow-up of implementation of differentiated learning depends on the teacher himself.